Mr. Kiasu : everything also what extra by - Johnny, Lau (1991)
A delightful Asian graphic book. "Everything also must grab." This is the new war cry for Mr. Kasu as he continue his fight to be the most 'kasu' person alive. This book is compulsory reading for anyone who is not familiar with the word 'KIASU'--the buzzword of the 90's"